Assessing the potential of iron oxide nanoparticles to treat cancer through magnetic hyperthermia - HANNON, GARY (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2020)
5-year survival for pancreatic cancer is about 10% worldwide. A subset of this cancer, pancreatic ductal adenocarcinoma (PDAC), is estimated to become the second leading cause of cancer-related deaths in the US by 2030. This cancer is commonly diagnosed late, so by the time the patient presents with symptoms, current treatments are ineffective against PDAC in its advanced stage. Research into novel therapies is therefore necessary to tackle this aggressive malignancy. Iron oxide nanoparticles (IONP) are small, magnetic materials with a variety of interesting properties that make them promising candidates for treating and diagnosing cancer. Upon exposure to external alternating magnetic fields, these materials can heat up and treat tumours through a procedure called magnetic hyperthermia. Moreover, this magnetic hyperthermia treatment can be incorporated into current treatment regimens for PDAC patients, where it has shown to enhance the effects of chemotherapy and radiation. Currently, an IONP called Nanotherm? is clinically approved to treat glioblastoma, an aggressive brain cancer, with magnetic hyperthermia. It has also shown promising results in trials for prostate cancer. This project follows the testing of new IONP to treat PDAC with magnetic hyperthermia. The nanoparticles were characterized, tested for their heating capabilities, assessed for endotoxin contamination and their potential to induce immunotoxicities in vitro and in vivo. This work was run in parallel to the work of collaborators with the hopes of contributing to a dossier for a clinical trial for these nanoparticles.
APPROVED
Keywords: Cancer; Toxicity; Iron oxide nanoparticles; Magnetic hyperthermia; Nanomedicine; Nanomaterials; Pancreatic cancer